A Multiliteracy Learning Model as a Means to Address Language Dysphemism in Elementary School Children - Riyanto, Sugeng (Insight School Academy, 2024)
Introduction to The Problem: Polite language creates positive value from speaking partners, while impolite language gives negative impressions. Purpose: This research aims to describe an appropriate multiliteracy learning model to address language dysphemia in elementary school children. Design/methods/approach: This study uses a qualitative approach based on Cresswell (2015:291). Data sources include interviews with classroom teachers implementing existential humanistic approaches, elementary students, and principals from public and private schools in Yogyakarta. Documentation includes audio-visual materials (photos, videotapes, recordings) and observations with field notes and reflections. Data validity follows Creswell and Miller's (2000) five criteria: data triangulation, member checking, prolonged observation with repeated site visits, and peer review. Findings: This multiliteracy learning model can develop speaking skills in elementary-age children accountably, as multiliteracy competency includes oral idea production ability. School programs supporting multiliteracy implementation must be systematic, flexible, realistic, and sustainable. Infrastructure requirements include libraries, reading corners, literacy centers, and teaching materials. Research implications/limitations: Multiliteracy concept reflects awareness of diverse human communication methods and literacy activities in analyzing received materials and media. This implies extensive critical analysis for text interpretation. School implementation can include DEAR programs promoting active participation through greetings, songs, and topic discussions to develop speaking, listening, interaction, and sharing abilities. Originality/value: This multiliteracy research presents novelty as an appropriate learning model for addressing impolite speech in students.